Disparitas Regulasi dan Implikasi Fiskal: Analisis Limitasi Peran Agen Visa Dalam Ekosistem Perpajakan Digital Nomad di Bali - Ni Putu Trisna Dewi; Desy Arlita (Ikatan Da'i Indonesia, 2026)
The phenomenon of digital nomads has created a new economic ecosystem while also giving rise to complex regulatory challenges, particularly in relation to tax and immigration compliance. Visa agencies have emerged as key mediators in bridging the needs of digital nomads with government bureaucracy. However, this position places them in a legal gray area and exposes them to various risks. This study aims to analyze the mediating role of visa agencies in promoting tax compliance among digital nomads in Bali, focusing on their risk perceptions and facilitation strategies. This study uses a qualitative approach with a case study design in the Canggu area of Bali. The results of this study are expected to provide an in-depth understanding of the strategies used by visa agencies in navigating their clients' tax compliance issues without acting as tax consultants. In addition, this study aims to formulate valuable input for policymakers to create more effective and clear regulations to support a sustainable digital nomad economic ecosystem in Bali.